ON CONTINUED CULTURE.TRIALS OF LATES CALCARIFER (BLOCH) AND OREOCHROMIS MOSSAMBICUS IN THE PONDS OF KHARLAND RESEARCH STATION, PANVEL, MAHARASHTRA - SINGH, R. K.; SHIRGUR, G. A. (Journal of Indian Fisheries Association, 2015)
Pond culture trials of Lates calcarifer (Bloch) were initiated in. theponds of Kharland .Research Station, Panvel, from 1985 upto 1989 byadopting varying methods of inputs of commonly available organicsubstaces comprising deoiled cake of groundnut, rice bran and raw cattledung. Although provision of zooplanldon generated under phasedfertilisation technique resuited in considerable yield level, subsequenttrials in combination with direct feed methods gave higher yield.Trials during 1990m91 adopting similar feed input techniques werecontinued but by stocking the seed of both Lates and Oreochromism,ossambicus with yield percentage around 72.23 for Lates and 27.73 forOreochromis. Trials were further continued during next three years. Inrelation to the organic input levels the yields rate for seven months periodwas in the range of 119.4 kglha to 250.4 kg/ha for Lates. In case ofOreochromis the yield rate varied between 28.5 to 153.32 kglha indicatingthe influence of differential stocking rates and size of the seed of twospecies.